The Role of 21st Century Digital Skills in Office Practices for Sustainable Education - Purasani, Hana Netti; Joyoatmojo, Soetarno; Indriayu, Mintasih; Sawiji, Hery (Economic Education Analysis Journal, 2024)
The office practice course uses a role-playing learning model to present real office situations in learning, learning is carried out in groups consisting of seven members who play seven office personnel. Each group member carries out office work alternately with flowing work. Management of letters and documents still uses manual methods such as recording in a correspondence agenda book which of course is no longer relevant to the development of 21st century learning that uses technology. ICT in office practice supports 21st century digital skills for sustainable education. Research objective: to determine the role of 21st century digital skills in office practices for sustainable education. The method used is descriptive research with a qualitative approach. Conclusion: office practices still use manual methods for managing letters and documents recorded in agenda books, no longer relevant to office management that utilizes technology and is not in accordance with 21st century digital skills for sustainable education. Educators as facilitators need to provide facilities for the use of ICT specifically designed according to the learning needs of office practice. Suggestion: The technology used can be continuously developed according to the needs of 21st century digital skills for sustainable education. In this study it also makes it easy for lecturers to prepare office practice materials and makes it easier to evaluate student assignments so as to facilitate the learning process.